Comparison of genotoxic effect between smokeless tobacco (Maras powder) users and cigarette smokers by the alkaline comet assay - KARSLI, SEHER (SAGE PUBLICATIONS LTD, 2009)
Maras powder (MP) is a kind of smokeless tobacco used in the south-eastern region of Turkey and in several other countries of Middle and Far East. The present study was performed to assess the impacts of MP and cigarette smoking on the possible DNA damaging effect. Alkaline comet assay, which is a reliable and an important tool in human biomonitoring studies in the area of genetic toxicology, was used in peripheral lymphocytes of MP users, cigarette smokers, and non-smokers while their frequencies of total comet scores (TCS) were evaluated. The mean TCS (+/-SD) frequency in the peripheral lymphocytes was 14.4 (+/-10.04) for MP users and 8.26 (+/-5.38), 5.94 (+/-3.87) for cigarette smokers (P < 0.05) and non-smoking control subjects, respectively (P < 0.001). There was no significant effect of daily consumption of MP and the duration of MP usage on comet frequencies. In reply to a wrong belief among MP users (the use of smokeless tobacco product is substantially less hazardous than cigarettes), the present study shows that the oral use of smokeless tobacco represents a genotoxic hazard which is even higher than the DNA damage observed in cigarette smokers. Therefore, habitual use of MP should be taken into account and could be considered unsafe, equally harmful, and it should not be viewed as a safe alternative to cigarettes.
Keywords: alkaline comet assay; DNA damage; genotoxic risk; smokeless tobacco; DNA-DAMAGE; BUCCAL MUCOSA; CANCER; SMOKING; CELLS; SNUS; NITROSAMINES; MICRONUCLEI; MORTALITY; SUDAN